2011
DOI: 10.1093/cid/cir435
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Evaluation of Tests for Diagnosis of Histoplasmosis

Abstract: The sensitivity of antigen detection in disseminated histoplasmosis is higher in immunocompromised patients than in immunocompetent patients and in patients with more severe illness. The sensitivity for detection of antigenemia is similar to that for antigenuria in disseminated infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
321
3
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(338 citation statements)
references
References 16 publications
6
321
3
8
Order By: Relevance
“…Serological assays for detection of antibodies to H. capsulatum are advantageous, as they are performed with an easily accessible specimen source (e.g., serum) and provide high specificity (Ͼ90%); however, false-negative results may occur for patients with recent infections and those with compromised immunity (3, 11). Furthermore, low-level seropositivity following exposure or resolved infection is not uncommon and may be diagnostically confounding.Among the many available laboratory methods, detection of H. capsulatum antigen (Ag), specifically with the MiraVista (MVista) Histoplasma Ag quantitative enzyme immunoassay (EIA) (MiraVista Diagnostics, Indianapolis, IN), provides a high level of sensitivity for clinical disease in both acute and disseminated cases of infection (75 to 80% and Ͼ90%, respectively) (3,11,12). Also, unlike other diagnostic methods, monitoring of quantitative Histoplasma antigen values in urine and/or serum can be used to follow treatment responses and to monitor disease progression (13,14).…”
mentioning
confidence: 99%
“…Serological assays for detection of antibodies to H. capsulatum are advantageous, as they are performed with an easily accessible specimen source (e.g., serum) and provide high specificity (Ͼ90%); however, false-negative results may occur for patients with recent infections and those with compromised immunity (3, 11). Furthermore, low-level seropositivity following exposure or resolved infection is not uncommon and may be diagnostically confounding.Among the many available laboratory methods, detection of H. capsulatum antigen (Ag), specifically with the MiraVista (MVista) Histoplasma Ag quantitative enzyme immunoassay (EIA) (MiraVista Diagnostics, Indianapolis, IN), provides a high level of sensitivity for clinical disease in both acute and disseminated cases of infection (75 to 80% and Ͼ90%, respectively) (3,11,12). Also, unlike other diagnostic methods, monitoring of quantitative Histoplasma antigen values in urine and/or serum can be used to follow treatment responses and to monitor disease progression (13,14).…”
mentioning
confidence: 99%
“…One patient had antigenemia and antigenuria and one patient had antigenuria alone. One patient had both positive histoplasma and blastomyces urinary antigens however due to high cross reactivity reactions of these fungi (as high as 90%) [6] as well as clinical picture; the patient was felt to have infectious process consistent with SPH. In one patient (case number 1), nodal material was sent for flow cytometry, which was negative for a monoclonal population of lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study on antigen detection in dogs with blastomycosis revealed a sensitivity value of 94% in urine specimens and a value of 87% in serum specimens [7]. A multicenter evaluation on histoplasmosis antigen detection revealed 91.8% of 158 patients with disseminated histoplasmosis, 83.3% of 6 patients with acute histoplamosis, 30.4% of 46 patients with sub-acute hisotplasmosis, and 87.5% of 8 patients with chronic pulmonary histoplasmosis; antigenemia was present in 100% of 31 tested cases of disseminated histoplasmosis [18]. In another study on Coccidioides antigen detection, antigenuria was detected in 50% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years other investigators have been approaching the problem of immunodiagnosis and have produced encouraging results with antigen detection assays as second-generation assays have been developed [7,[14][15][16][17][18]. Our laboratory has been focusing on the use of the competitive enzyme-linked immunosorbent assay (ELISA) in B. dermatitidis antigen detection studies in urine specimens from dogs with diagnosed blastomycosis [11].…”
Section: Introductionmentioning
confidence: 99%